INTEGRATING CRITICAL THINKING TASKS INTO ENGLISH LANGUAGE TEACHING AT SCHOOL LEVEL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In recent years, the development of critical thinking has become one of the key objectives of modern education, particularly in foreign language teaching. Traditional approaches to English language teaching at the school level often emphasize memorization, grammar accuracy, and textbook-based activities, which may limit learners’ ability to analyze, evaluate, and use language meaningfully. This article explores the integration of critical thinking tasks into English as a Foreign Language (EFL) instruction at the school level and examines their impact on students’ engagement and language development.